1999
DOI: 10.1352/0895-8017(1999)104<0376:dpobfi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Pattern of Behavioral Functioning in Angelman Syndrome

Abstract: Angelman syndrome is a neurogenetic disorder that is characterized by impairments in neurological, motor, and intellectual functioning. This study compared 27 participants with Angelman syndrome to clinical and community participants with developmental disabilities of mixed etiology to determine whether Angelman syndrome is associated with a distinctive pattern of behavioral functioning. The groups with and without Angelman syndrome were matched on chronological age, gender, and level of intellectual functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…There are four studies that have attempted to systematically measure the behaviours of people with Angelman syndrome, using four different questionnaires (Summers et al, 1995;Summers & Feldman, 1999;Clarke & Marston, 2000;Walz & Benson, 2002). In order to further consider the notion of a behavioural phenotype for Angelman syndrome, these four studies will be briefly described and critically examined.…”
Section: ++++++++++++ Insertmentioning
confidence: 99%
See 4 more Smart Citations
“…There are four studies that have attempted to systematically measure the behaviours of people with Angelman syndrome, using four different questionnaires (Summers et al, 1995;Summers & Feldman, 1999;Clarke & Marston, 2000;Walz & Benson, 2002). In order to further consider the notion of a behavioural phenotype for Angelman syndrome, these four studies will be briefly described and critically examined.…”
Section: ++++++++++++ Insertmentioning
confidence: 99%
“…In both Summers and Feldman's (1999) and Walz and Benson's (2002) studies, it was not explored whether different phenotypic differences occurred across genetic sub types. Smith, Wiles, Haan, McGill, Wallace, Dixon, Selby, Golley, Marks, and Trent (1996) suggested that there is a distinct phenotype associated with a deletional Angelman syndrome consisting of: intellectual disability, ataxia, lack of speech, happy disposition and epilepsy.…”
Section: ++++++++++++ Insertmentioning
confidence: 99%
See 3 more Smart Citations